Manajemen Sumber Daya Manusia (MSDM) dalam Perspektif Ekonomi Syariah: Studi Kritis Aplikasi MSDM pada Lembaga Keungan Publik Islam - Abd. Ghofur, Ruslan (MUQTASID, 2010)
This Paper tries to discuss about the Islamic concept dealing with the human resource management issues. Sharia Management offers a solution by returning back to Islamic morals so that the formed social system is in line with Islamic teachings that create a conducive environment to carry out worship, to enact or practice law and to apply the ethics of Islam, which resulted in the creation of social systems that promote justice. The creation of these conditions are believed to always makesÂ  an individual (a muslim) in the awareness that Allah is always with him in every step so that whatever was done would be held its accountability and the formed values will create the Islamic ethics in a society that will always be practiced wherever he goes and lives, both inside and outside the organization. Keywords: management, human resource, ethics of Islam